Estimates of case-fatality ratios of measles in low-income and middle-income countries: a systematic review and modelling analysis. Issue 4 (April 2019) - Portnoy, Allison; Jit, Mark; Ferrari, Matthew; Hanson, Matthew; Brenzel, Logan; Verguet, Stéphane
Summary: Background: In the 21st century, increases in immunisation coverage and decreases in under-5 mortality have substantially reduced the global burden of measles mortality. However, the assessment of measles mortality burden is highly dependent on estimates of case-fatality ratios for measles, which can vary according to geography, health systems infrastructure, prevalence of underlying risk factors, and measles endemicity. With imprecise case-fatality ratios, there is continued uncertainty about the burden of measles mortality and the effect of measles vaccination. In this study, we aimed to update the estimations of case-fatality ratios for measles, to develop a prediction model to estimate case-fatality ratios across heterogeneous groupings, and to project future case-fatality ratios for measles up to 2030. Methods: We did a review of the literature to identify studies examining measles cases and deaths in low-income and middle-income countries in all age groups from 1980 to 2016. We extracted data on case-fatality ratios for measles overall and by age, where possible. We developed and examined several types of generalised linear models and determined the best-fit model according to the Akaike information criterion. We then selected a best-fit model to estimate measles case-fatality ratios from 1990 to 2015 and projected future case-fatality ratios for measles up to 2030. Findings: We selected 124 peer-reviewed journal articles published between Jan 1, 1980, and Dec 31, 2016, for inclusion in the final review—85 community-based studies and 39 hospital-based studies. We selected a log-linear prediction model, resulting in a mean case-fatality ratio of 2·2% (95% CI 0·7–4·5) in 1990–2015. In community-based settings, the mean case-fatality ratio was 1·5% (0·5–3·1) compared with 2·9% (0·9–6·0) in hospital-based settings. The mean projected case-fatality ratio in 2016–2030 was 1·3% (0·4–3·7). Interpretation: Case-fatality ratios for measles have seen substantial declines since the 1990s. Our study provides an updated estimation of case-fatality ratios that could help to refine assessment of the effect on mortality of measles control and elimination programmes. Funding: Bill & Melinda Gates Foundation.